Q. 505.0( 1 Vote )

# Solve: √3x2 – 2√2x – 2√3 = 0

Using splitting middle term, the middle term of the general equation is divided in two such values that:

Product = a.c

For the given equation

using

=

And either of their sum or difference = b

=

Thus the two terms are

Difference =

Product = = - 6

√3 x(x-√6) + √2(x-√6) = 0

(√3 x + √2)(x-√6) = 0

(√3 x + √2) = 0 or (x-√6) = 0

Hence roots of equation are

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Quiz | Knowing the Nature of Roots44 mins
Take a Dip Into Quadratic graphs32 mins
Foundation | Practice Important Questions for Foundation54 mins
Nature of Roots of Quadratic EquationsFREE Class
Getting Familiar with Nature of Roots of Quadratic Equations51 mins
Quadratic Equation: Previous Year NTSE Questions32 mins
Champ Quiz | Quadratic Equation33 mins
Balance the Chemical Equations49 mins
Champ Quiz | Quadratic Equation48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses